Pilot study Al-Maahirah app in enhancing Arabic learning: A case study at Al-Khairiyah High School, Indonesia - Naqiyah, Neni; Muassomah, Muassomah; Mufidah, Nuril (Abjadia : International Journal of Education, 2025)
The Arabic language proficiency of students at Al-Khairiyah Senior High School Kelapian Banten appears to be hindered by several factors, including a lack of interactive learning tools such as Android-based applications, gaps in instructional content, low student engagement, limited teacher training, and the absence of supplementary educational resources like LKPD. Even though Azzahra stated, that Android-based Arabic language worksheets are quite effective in improving students' Arabic learning outcomes. A study was conducted to evaluate the impact of the "Al-Maahirah" application on the Arabic learning performance of tenth-grade students at the school. The research utilized a quantitative experimental approach, specifically a pre-experimental design with a one-group pretest-posttest method. The sample consisted of 13 students, with data collected through assessments and analyzed using the Wilcoxon test and the N-Gain test. The results indicated that the Asymp. Sig. (2-tailed) value was 0.001, which is below 0.05, suggesting a significant difference between pretest and posttest scores. Moreover, the results of the N-Gain test showed a score of 0.715 or in percentage form 71.5%, which interprets a high score, and an effective score of 0.89824, which is included in the large category. Based on these findings, it was determined that the "Al-Maahirah" application contributed significantly to improving students' Arabic language learning outcomes during the 2024-2025 academic year.